2010
DOI: 10.1016/j.chc.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Development and Vulnerability Factors in Adolescent Alcohol Use

Abstract: This article provides an overview of the characteristics of adolescent alcohol use, normative and subgroup variations in drinking behavior, and important factors associated with an increased risk for developing alcohol problems in later adolescence and young adulthood. A parental/family history of alcoholism, temperament traits, conduct problems, cognitive functioning, alcohol expectancies, and peer and other social relations are identified as influencing an adolescent's susceptibility for initiating a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 72 publications
5
70
1
8
Order By: Relevance
“…These results were similar to those reported by Chartier, Hesselbrock, and Hesselbrock (2010) based on the results of the 2007 National Survey on Drug Use and Health in the United States, which showed strong correlations be-tween stressful life events, abuse during childhood, domestic violence, and lack of social resources in families who experienced alcoholism, depressive symptoms, and behavioral problems. Consistent with these findings, the results of the current study showed that the lack of parental control during childhood was particularly strongly correlated with the abuse of substances, including alcohol.…”
Section: Child-rearing Environment and Primary Addictionsupporting
confidence: 79%
“…These results were similar to those reported by Chartier, Hesselbrock, and Hesselbrock (2010) based on the results of the 2007 National Survey on Drug Use and Health in the United States, which showed strong correlations be-tween stressful life events, abuse during childhood, domestic violence, and lack of social resources in families who experienced alcoholism, depressive symptoms, and behavioral problems. Consistent with these findings, the results of the current study showed that the lack of parental control during childhood was particularly strongly correlated with the abuse of substances, including alcohol.…”
Section: Child-rearing Environment and Primary Addictionsupporting
confidence: 79%
“…To our knowledge, this combination of adolescent development, bi-directional relationships between an addiction-associated phenotype and drug intake, and a signature neurobiological feature of addiction (reduced striatal D2 receptors) is unique among animal models linking addiction-associated traits and drug use (Belin et al, 2008;Besson et al, 2010;Dalley et al, 2007;Robinson, 2010, 2011). In particular, because predispositions for drug use can be evident in human adolescence (Chambers et al, 2003;Chartier et al, 2010), the ability to capture a predictive phenotype at this stage of development is important for modeling vulnerability to drug use. However, it is also notable that several other adult rodent models of addiction-associated phenotypes, particularly those related to impulsive behavior, predict aspects of cocaine SA that are more closely linked to addiction than acquisition (eg, enhanced motivation to selfadminister, resistance to extinction; Anker et al, 2009;Belin et al, 2008;Dalley et al, 2007;Perry et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Impulsive individuals, determined using either personality-or performance-based criteria, initiate drug use at earlier ages, escalate to heavy use, and transition to abuse and dependence more quickly and are less likely to remain abstinent after treatment compared with nonimpulsive individuals (de Wit, 2009;Dick et al, 2010;Dalley et al, 2011). Longitudinal studies of early childhood temperament indicate that the association between impulsivity and vulnerability to drug abuse is present at an early age (Zucker et al, 2008;Chartier et al, 2010). Thus, individuals who are high in impulsivity are likely to engage in a variety of risky behaviors, including drug use, and are more sensitive to the reinforcing and other pharmacodynamic effects of drugs after initial use, thereby making them more inclined to continue and escalate drug use.…”
Section: A Individual Differencesmentioning
confidence: 99%